Accumulated Epinephrine Dose is Associated With Acute Kidney Injury Following Resuscitation in Adult Cardiac Arrest Patients - Gao, Qiang; Mok, Hsiao-Pei; Qiu, Hai-Long; Cen, Jianzheng; Chen, Jimei; Zhuang, Jian (Frontiers in Pharmacology, 2022)
The goal of this study was to investigate the association between total epinephrine dosage during resuscitation and acute kidney injury after return of spontaneous circulation in patients with cardiac arrest. We performed a secondary analysis of previously published data on the resuscitation of cardiac arrest patients. Bivariate, multivariate logistic regression, and subgroup analyses were conducted to investigate the association between total epinephrine dosage during resuscitation and acute kidney injury after return of spontaneous circulation. A total of 312 eligible patients were included. The mean age of the patients was 60.8 ± 15.2 years. More than half of the patients were male (73.4%) and had an out-of-hospital cardiac arrest (61.9%). During resuscitation, 125, 81, and 106 patients received ≤ 2, 3 - 4, and ≥ 5 mg epinephrine, respectively. After return of spontaneous circulation, there were 165 patients (52.9%) and 147 patients (47.1%) with and without acute kidney injury, respectively. Both bivariate and multivariate analysis showed a statistically significant association between total epinephrine dosage and acute kidney injury. The subgroup analysis showed that the strength of the association between epinephrine dosage and acute kidney injury varied by location of cardiac arrest. Further multivariate regression analysis found that the association between epinephrine dosage and acute kidney injury was only observed in patients with in-hospital cardiac arrest after adjusting for multiple confounding factors. Compared with in-hospital cardiac arrest patients who received ≤ 2 mg of epinephrine, patients with 3 - 4 mg of epinephrine or ≥ 5 mg of epinephrine had adjusted odds ratios of 4.2 (95% confidence interval 1.0-18.4) and 11.3 (95% confidence interval 2.0 - 63.0), respectively, to develop acute kidney injury. Therefore, we concluded that a higher epinephrine dosage during resuscitation was associated with an increased incidence of acute kidney injury after return of spontaneous circulation in adult patients with in-hospital cardiac arrest.